2020
DOI: 10.1177/0013164420940764
|View full text |Cite
|
Sign up to set email alerts
|

Examining Multidimensional Measuring Instruments for Proximity to Unidimensional Structure Using Latent Variable Modeling

Abstract: A widely applicable procedure of examining proximity to unidimensionality for multicomponent measuring instruments with multidimensional structure is discussed. The method is developed within the framework of latent variable modeling and allows one to point and interval estimate an explained variance proportion-based index that may be considered a measure of proximity to unidimensional structure. The approach is readily utilized in educational, behavioral, and social research when it is of interest to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…First, the inspection of the pattern showed that it exhibited positive manifold (i.e., all the loadings were substantial and positive). Second, the ECV estimate was .789 (bootstrap 95% CI = 0.764 and 0.815), above the 0.70 usual cutoff for judging a unidimensional approximation as reasonable (Raykov & Bluemke, 2021; Reise et al, 2013). Indeed, approximating a multidimensional structure by a unidimensional solution potentially presents the underfactoring problems discussed above: biased “mixture” loading estimates that would reflect the differential influence of the local factors, loss of information, and scores reflecting the influence of multiple sources of variance.…”
Section: Illustrative Examplementioning
confidence: 88%
“…First, the inspection of the pattern showed that it exhibited positive manifold (i.e., all the loadings were substantial and positive). Second, the ECV estimate was .789 (bootstrap 95% CI = 0.764 and 0.815), above the 0.70 usual cutoff for judging a unidimensional approximation as reasonable (Raykov & Bluemke, 2021; Reise et al, 2013). Indeed, approximating a multidimensional structure by a unidimensional solution potentially presents the underfactoring problems discussed above: biased “mixture” loading estimates that would reflect the differential influence of the local factors, loss of information, and scores reflecting the influence of multiple sources of variance.…”
Section: Illustrative Examplementioning
confidence: 88%
“…The study further examined the validity of the TIOSS for explaining the validity of the scale and its predictive effect on actual behavior [56]. In previous studies, occupational stigma was observed to be negatively influencing the organizational atmosphere as well as practitioners' work attitudes, behaviors, intergroup relations, professional identity, and psychological well-being [57].…”
Section: Discussionmentioning
confidence: 99%
“…If analysis models are multidimensional (assuming no crossloadings), separate MIVIs should be used for each subscale. Alternatively, one might estimate how proximate the multidimensional model is to a unidimensional one, indicating whether the multidimensional model can be treated as essentially unidimensional (Raykov & Bluemke, 2020). Extensions of MIVI for multidimensional scales are conceivable but beyond the scope of the present demonstration.…”
Section: Quantifying Scalar Non-invariance Bias 24mentioning
confidence: 95%